Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10955-005-3021-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation Relation beyond Linear Response Theory

Abstract: The Fluctuation Relation (FR) is an asymptotic result on the distribution of certain observables averaged over time intervals τ as τ → ∞ and it is a generalization of the fluctuation-dissipation theorem to far from equilibrium systems in a steady state which reduces to the usual Green-Kubo (GK) relation in the limit of small external non conservative forces. FR is a theorem for smooth uniformly hyperbolic systems, and it is assumed to be true in all dissipative "chaotic enough" systems in a steady state. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…The numerical results of [34][35][36] agree with the prediction that FR for the rate function of a 0 is valid even beyond a 0 = σ + . The prediction that (at least near equilibrium) the rate function of a should satisfy FR only up to a = σ + and that should become linear for a ≥ a + at the moment has been experimentally confirmed only in Gaussian cases [4,24,25].…”
Section: How To Remove Singularitiessupporting
confidence: 76%
See 2 more Smart Citations
“…The numerical results of [34][35][36] agree with the prediction that FR for the rate function of a 0 is valid even beyond a 0 = σ + . The prediction that (at least near equilibrium) the rate function of a should satisfy FR only up to a = σ + and that should become linear for a ≥ a + at the moment has been experimentally confirmed only in Gaussian cases [4,24,25].…”
Section: How To Remove Singularitiessupporting
confidence: 76%
“…It would be very interesting to investigate in detail the structure of ζ(a) even in non Gaussian cases. Note that this is far from being an easy task (in particular the analysis in [36] was not sophisticated enough to study this problem). In fact, as discussed in detail in [35], the presence in the definition of σ of a total derivative of an unbounded function may enlarge of 2 orders of magnitudes the times needed for the probability distribution of a to reach its asymptotic shape: even in the Gaussian region (small fluctuations of a around σ + ) the convergence times for ζ(a) are found to be of order 1000 decorrelation times, versus a time of order 10 decorrelation times needed for ζ 0 (a 0 ) to converge to its asymptotic shape [35].…”
Section: How To Remove Singularitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [49] it was noted that, using Eq.s (19) and (20), it turns out that the non Gaussian term in (19) is proportional to J (3) ∞ E 3 (p − 1) 3 ; this suggested that, keeping fixed E to have a small σ + , one could increase the non Gaussian tails of ζ ∞ (p) by increasing J (3) ∞ , which is related to the nonlinear part of the transport coefficient. In a fluid of Lennard-Jones like particles, the nonlinear response is observed to increase on lowering the temperature: this fact was exploited in [49] where it was possible to verify the fluctuation relation in a numerical simulation on a non Gaussian ζ ∞ (p), see figure 2.…”
Section: Summary and A Review Of Numerical Resultsmentioning
confidence: 99%
“…Unfortunately, 1) is limited by the fact that the fluctuation relation holds only for large τ , i.e. τ ≫ τ 0 ; so we can reduce τ , but at best we can use τ ∼ 100τ 0 if we do not want to observe finite τ effects [48,49]. Note also that in experiments τ is strongly constrained by the acquisition bandwidth.…”
Section: Entropy Production Ratementioning
confidence: 99%